2014
DOI: 10.1167/iovs.14-14246
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Age-Related Macular Degeneration in Diverse Populations From the PAGE Study

Abstract: While most associations did not generalize in the non-European populations, variants within lipid-related genes were found to be associated with AMD. This study highlights the need for larger well-powered studies in non-European populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 78 publications
(100 reference statements)
0
36
0
Order By: Relevance
“…In addition, race appears to impact the role of various genetic influences on AMD (Restrepo et al, 2014). The effect of different genetic variants on AMD among different racial or ethnic groups will be discussed later.…”
Section: Biomarkers Of Susceptibilitymentioning
confidence: 99%
“…In addition, race appears to impact the role of various genetic influences on AMD (Restrepo et al, 2014). The effect of different genetic variants on AMD among different racial or ethnic groups will be discussed later.…”
Section: Biomarkers Of Susceptibilitymentioning
confidence: 99%
“…Since the allelic frequency and associations of CFH and ARMS2 polymorphisms with AMD may vary across populations, genetic analyses were further stratified by race. (33) Similarly, to assess for effect modification by HDL, HDL2, HDL3, and apoA1, analyses of the associations between visit 1 xanthophyll intake (tertiles) and AMD status were stratified by the sample medians of these lipid biomarkers. P-values <0.10 were considered statistically significant when testing for multiplicative interaction.…”
Section: Methodsmentioning
confidence: 99%
“…The Population Architecture Using Genomics and Epidemiology (PAGE) study demonstrated that AMD risk appears to differ with respect to lipid metabolism and cholesterol-related genes in Mexican Americans, Asian Americans, African Americans, and non-Hispanic White Europeans when all types of AMD were examined [52]. In fact, in this study, none of the major risk variants for AMD e.g., HtrA serine peptidase 1 ( HTRA1)/age-related maculopathy susceptibility 2 (ARMS2) or complement factor H ( CFH ), were significant in the non-white European populations after correction for multiple testing, but this was likely due to the small sample size used in this study [52]. However, Cheng et al found a novel variant in the CETP gene as well as novel AMD lipid/cholesterol genes associated with AMD risk in East Asians [92].…”
Section: Genome-wide and Candidate Gene Association Studies Of Amdmentioning
confidence: 99%
“…While GWAS and epidemiological studies have implicated the lipid metabolism-cholesterol pathway in AMD pathophysiology, the role is unclear and at times inconsistent [52, 53]. Given the variances within and among ethnic populations with respect to AMD genetics, prevalence, and pathology, further effort needs to be focused on working out the population-specific molecular mechanisms that may influence individual patient responses to therapeutic interventions and progression of the disease.…”
Section: Genome-wide and Candidate Gene Association Studies Of Amdmentioning
confidence: 99%